Potential of Fibrin Glue and Mesenchymal Stem Cells (MSCs) to Regenerate Nerve Injuries: A Systematic Review - Ortiz, Adriana de Cássia; Fideles, Simone Ortiz Moura; Pomini, Karina Torres; Bellini, Márcia Zilioli; Pereira, Eliana de Souza Bastos Mazuqueli; Reis, Carlos Henrique Bertoni; Pilon, João Paulo Galletti [UNESP]; de Marchi, Miguel Ângelo; Trazzi, Beatriz Flavia de Moraes; da Silva, Willian Saranholi; da Cunha, Marcelo Rodrigues; Buchaim, Daniela Vieira; et al. (MDPI, 2022)
Cell-based therapy is a promising treatment to favor tissue healing through less invasive strategies. Mesenchymal stem cells (MSCs) highlighted as potential candidates due to their angio-genic, anti-apoptotic and immunomodulatory properties, in addition to their ability to differentiate into several specialized cell lines. Cells can be carried through a biological delivery system, such as fibrin glue, which acts as a temporary matrix that favors cell-matrix interactions and allows local and paracrine functions of MSCs. Thus, the aim of this systematic review was to evaluate the potential of fibrin glue combined with MSCs in nerve regeneration. The bibliographic search was performed in the PubMed/MEDLINE, Web of Science and Embase databases, using the descriptors (“fibrin sealant” OR “fibrin glue”) AND “stem cells” AND “nerve regeneration”, considering articles published until 2021. To compose this review, 13 in vivo studies were selected, according to the eligibility criteria. MSCs favored axonal regeneration, remyelination of nerve fibers, as well as promoted an increase in the number of myelinated fibers, myelin sheath thickness, number of axons and expression of growth factors, with significant improvement in motor function recovery. This systematic review showed clear evidence that fibrin glue combined with MSCs has the potential to regenerate nervous system lesions.
Keywords: Fibrin glue; Fibrin sealant; Nerve regeneration; Scaffolds; Stem cells; Systematic review